Productivity, photosynthetic light-use efficiency, nitrogen metabolism and nutritional quality of C4 halophyte Portulaca oleracea L. grown indoors under different light intensities and durations - He, Jie; Gan, Jia Hui Shirin; Qin, Lin (Frontiers in Plant Science, 2023)
Portulaca oleracea L. (known as purslane), is a nutritious facultative C4 halophyte. Recently, it has been successfully grown indoors under LED lightings by our team. However, basic understanding about the impacts of light on purslanes are lacking. This study aimed to investigate the effects of light intensity and duration on productivity, photosynthetic light use efficiency, nitrogen metabolism and nutritional quality of indoor grown purslanes. All plants were grown in 10% artificial seawater hydroponically under different photosynthetic photon flux densities (PPFDs) and durations and thus different daily light integrals (DLI). They are, L1 (240 µmol photon m-2 s-1, 12 h, DLI = 10.368 mol m-2 day-1); L2 (320 µmol photon m-2 s-1, 18 h, DLI = 20.736 mol m-2 day-1); L3 (240 µmol photon m-2 s-1, 24 h, DLI = 20.736 mol m-2 day-1); L4 (480 µmol photon m-2 s-1, 12 h, DLI = 20.736 mol m-2 day-1), respectively. Compared to L1, higher DLI promoted root and shoot growth and thus increased shoot productivity by 2.63-,1.96-, 3.83-folds, respectively for purslane grown under L2, L3, L4. However, under the same DLI, L3 plants (continuous light, CL) had significantly lower shoot and root productivities compared those with higher PPFDs but shorter durations (L2 and L4). While all plants had similar total chlorophyll and carotenoid concentrations, CL (L3) plants had significantly lower light use efficiency (Fv/Fm ratio), electron transport rate, effective quantum yield of PSII, photochemical- and non-photochemical quenching. Compared to L1, higher DLI with higher PPFDs (L2 and L4) increased leaf maximum nitrate reductase activity while longer durations increased leaf NO3 concentrations and total reduced nitrogen. There were no significant differences in leaf total soluble protein, total soluble sugar and total ascorbic acid concentrations in both leaf and stem regardless of light conditions. However, L2 plants had the highest leaf proline concentration but leaf total phenolic compounds concentration was higher in L3 plants instead. Generally, L2 plants had the highest dietary minerals such as K, Ca, Mg and Fe among the four different light conditions. Overall, L2 condition is the most suitable lighting strategy in enhancing productivity and nutritional quality of purslane.